WOMEN’S READINGS IN MEDIEVAL LITHUANIA: GRAND DUCHESS ONA AND DARATA’S “LIFE” - Drungilienė, Gita (Knygotyra, 2016)
At the time of her visit to Marienwerder in 1400, Ona (d. 1418), the wife of Vytautas the Great, Grand Duke of Lithuania, was given two books about the life of the Blessed Dorothea of Montau (1347–1394); this information was preserved in the documents of Dorothea’s canonization process. This is, in effect, the first mention of book ownership by a woman in the GDL. Based on the documents of Dorothea’s canonization and other sources, the article aims to discuss what books, and in what circumstances, Grand Duchess Ona received and how this reflects her personality. The article looks at the Prussian mystic Dorothea of Montau, her spirituality and her cult, whose echoes reached Lithuania; it discusses the books written by Dorothea’s confessor, the hagiographer Johannes of Marienwerder (finished in 1399 or 1400), which make the repertoire of “dorotheana”. The article analyses Ona’s visit to Marienwerder, the event mentioned by 13 witnesses in Dorothea’s canonization case in their answer to the question (No. 146) about Dorothea’s fama sanctitatis. The present research has shown that, at the turn of the 14th century, Grand Duchess Ona found herself in the midst of the novel, speedily growing cult of Dorothea of Montau. It found a place in Ona’s heart and became upheld by other members of Lithuania’s ruling elite. A tale about the life of the woman renowned for her sanctity, heard from the theologian Johannes himself, encouraged Ona’s interest in the book describing the life and piety of Dorothea, a representative of the new women’s spirituality. This “life” of the yet-uncanonized saint, Dorothea from Montau, may be considered one of the first hagiographic pieces of the vita type, functioning in the GDL. Both the pilgrimage of the Duchess Ona and the books given to her are a testimony to her worship of saints, practiced in various forms and characteristic of the Middle Ages, as well as to her interest in the lives of saints.
Keywords: ...